Towards An Islamic Application Of Visual Privacy Principles On Malaysian Terrace Housing: A Conceptual Framework - Azhani Abd Manaf; Zaiton Abdul Rahim; Noor Hanita Abdul Majid; Spahic Omer (Malaysian Institute of Planners, 2024)
PLANNING MALAYSIA:Journal of the Malaysian Institute of Planners VOLUME 16 ISSUE 2 (2018), Page 1 -11